Teatro de Reprise telepresencial em tempos de COVID-19 - Rodrigues, Rosane; Coutinho, Eduardo Tessari; Barêa, Janaína Cristina; Oliveira e Aguiar, Alexandre de (Revista Brasileira de Psicodrama, 2020)
In times of quarantine due to COVID-19, it is essential to explore tools to face the psychosocial challenges caused by social isolation and new routines. It is worth emphasizing to seek ways for meeting the needs of getting together, taking advantage of technological resources. The objective of this work is to present and discuss an adaptation of the Reprise Theater with telepresence resources. We used the method of action research. The specific intervention was an initiative by a group of users of a cultural center, where face-to-face Public Psychodramas regularly occur. As from the psychodrama view, this paper discusses the implications and possibilities of using a technological platform, the roles of the people involved, and the possibility of new sociometries, in an intervention.